Penerapan Teknik UV Mapping dan Texture Painting Dalam Pembuatan Film Animasi 3D Bujang Buta - M Iqbal Setiawan; Anggy Trisnadoli; Erwin Setyo Nugroho (Diponegoro University, 2019)
The use of UV Mapping and Texture Painting Technique in Indonesia is a country that is rich in folklore. Bujang Buta is one of the folklore originating from the city of Kampar. Many people do not know about the existence of detailed folklore. In this study raised the Bujang Buta folklore which will be attractively packaged in the form of 3D animated films. In the 3D animation film there are many techniques to make it, one of which is the UV Mapping and Texture Painting techniq ues that make 3D animated films more colorful. Making this animated film uses the Blender 3D application as its main medium. Based on the results of testing and analysis, the 3D animated film Bujang Buta Folklore has been verified by LAMR experts (Lembaga Adat Melayu Riau). The UV Mapping and Texture Painting technique has been successfully implemented into the making of the Bujang Buta 3D animated film. And based on the results of a questionnaire that has been given to 37 general public and 6 people who fo llow the organization there are 10 moral messages in the 3D animated film Bujang Buta.